Aspectos fluidodinâmicos de misturas binárias de resíduo de tabaco e areia em leito fluidizado - Oliveira, Tiago José Pires de (2012)
Currently seeking new forms to meet the world\'s energy needs and biomass is an alternative to supply as a source of renewable energy and cleaner. The fluidized bed reactors are widely used for the production of fuel gas, syngas and products such as methanol, bio-oil, etc. Due to its good gas-solid contact, high rates of heat and mass transfer, the beds fludizeds options has become effective for the realization of fast pyrolysis because they favor the physical and chemical processes that occur during pyrolysis. In the fast pyrolysis of biomass in bubbling fluidized bed, the sand is used to ensure homogeneity of mixing and high heat transfer coefficients. These characteristics are fundamental to the kinetics of thermal decomposition of biomass. The fluidization of mixtures of sand and biomass is characterized by particles of different shapes, sizes, densities and compositions (amount of each solid). Therefore this work was to study the fluid-dynamic behavior of the fluid and particles within the bed, and the main objective to determine the minimum fluidization velocities of binary mixtures of biomass and inert. We investigated the fluid dynamics of mixtures of particles fluidized in order to determine an initial composition which mitigates the segregation effect. The segregation is characterized by the difference of the terminal velocity of the particles that make up the mixture, a fact that may occur due to the difference of densities and particle sizes. Therefore, experiments with mixtures of biomass and inert were conducted by varying the composition of biomass and the main fluid dynamic information were measured. The materials used were the work of the stalk of tobacco dust and sand Brazilian standard normal (IPT). Regarding the parameters studied in the fluid dynamics of mixtures, the experiments allowed a better understanding of the mechanisms of segregation. Overall, in all mixtures used in the experiments we observed a concentration of inert along the bottom, whereas the biomass, less dense, concentrated mainly at the top of the annular region. As for the percentage by weight of biomass, which in the experiments were 5, 10 and 15%, it was observed that for mixtures with 15% of biomass is the formation of preferential channels, packing the bed and the presence of bubbles. The minimum fluidization velocities of these binary mixtures were obtained experimentally and the values were compared with some correlations reported in the literature.